2016
DOI: 10.1002/anie.201606774
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophile‐Directed Stereocontrol Over Glycosylations Using Geminal‐Difluorinated Nucleophiles

Abstract: The glycosylation reaction is the key transformation in oligosaccharide synthesis, but it is still difficult to control in many cases. Stereocontrol during cis‐glycosidic linkage formation relies almost exclusively on tuning the glycosylating agent or the reaction conditions. Herein, we use nucleophile‐directed stereocontrol to manipulate the stereoselectivity of glycosylation reactions. Placing two fluorine atoms in close proximity to the hydroxy group of an aliphatic amino alcohol lowers the oxygen nucleophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…While the reactive primary alcohol 156 provided a b-selective reaction, the weaker nucleophile 157 mainly provided the a-product (Scheme 4). 75 By tweaking the reaction temperature and solvent, nearly complete aor b-stereoselectivity could be obtained. 76 A variety of different donors provided a similar reactivity-stereoselectivity trend.…”
Section: Systematic Studies On Acceptor Reactivitymentioning
confidence: 99%
“…While the reactive primary alcohol 156 provided a b-selective reaction, the weaker nucleophile 157 mainly provided the a-product (Scheme 4). 75 By tweaking the reaction temperature and solvent, nearly complete aor b-stereoselectivity could be obtained. 76 A variety of different donors provided a similar reactivity-stereoselectivity trend.…”
Section: Systematic Studies On Acceptor Reactivitymentioning
confidence: 99%
“…[4] Ther eactivity of acceptor glycosides is less well understood and systematic studies investigating this important reaction parameter are extremely scarce. [6] Often, this is done in atime consuming,trial-anderror manner since well-defined guidelines on how to tune the reactivity of an acceptor and how this effects the glycosylation reaction are absent. [6] Often, this is done in atime consuming,trial-anderror manner since well-defined guidelines on how to tune the reactivity of an acceptor and how this effects the glycosylation reaction are absent.…”
mentioning
confidence: 99%
“…[5] At the same time,i ti sc ommon practice to change protecting groups on the acceptor building block to influence the yield or change the stereoselectivity of ag lycosylation reaction. [6] Often, this is done in atime consuming,trial-anderror manner since well-defined guidelines on how to tune the reactivity of an acceptor and how this effects the glycosylation reaction are absent. [7] Recently,w eh ave shown that the reactivity of the acceptor can have aprofound influence on the stereochemical outcome of ag lycosylation reaction.…”
mentioning
confidence: 99%
“…Seeberger was honored for his work on automated sugar synthesis for the development of vaccines, therapies, and diagnostics. He has reported in Angewandte Chemie on nucleophile‐directed stereocontrol over glycosylation reactions, and is co‐author of a report in ChemPlusChem on glucose‐modified silica nanoparticles . Seeberger is on the Editorial Advisory Board of ChemBioChem .…”
Section: Awarded …mentioning
confidence: 99%